Semiotics Analysis The Art Work By Aliansyah Chaniago Entitled Lanscape Of Barus - Hismanto, Andi (VCD: Journal of Visual Communication Design, 2019)
The art works have visual and verbal symbols signifying language phenomena. Art works such as paintings can also be called sign phenomena. The sign or symbol used by artists in creating a painting is the process of contemplation, feeling and artists' thoughts about the environment. The art installation by Aliansyah Chaniago entitled "Lanscape of Barus" conveys a message in a form of symbols hidden in the art work. That is the message about Aliansyah Chaniago’s memory on the Barus tree in his hometown. The method used to understand the value in Aliansyah's work is the method of interpretation analysis. Symbols that appear in the work of Aliansyah Caniago show the efforts of Aliansyah Caniago to provide information about the City of Barus and its glory, as well as the effects of excessive exploitation on natural richness in the future.